The Role of the Patients' Companion in the Transitional Care from the Open Heart Surgery ICU to the Cardiac Surgery Ward: A Qualitative Content Analysis - Sahar Khoshkesht; Shahrzad Ghiyasvandian; Maryam Esmaeili; Masoumeh Zakerimoghadam (Shiraz University of Medical Sciences, 2021)
Background: The patients' companions can help improve transitional care as an important missinglink, but their role is not clear. The aim of this study was to explore the role of the patients' companionin the transitional care from the open heart surgery intensive care unit (OH-ICU) to the cardiac surgeryward.Methods: This was a qualitative descriptive study using conventional content analysis that wasconducted from September 2019 to February 2020 in Tehran, Iran. Purposeful sampling method withmaximum variation was performed among the patients eligible for transfer to the cardiac surgeryward, their companions, nurses, and physicians in charge of transferring from the OH-ICU to theward. 27 in-depth and semi-structured interviews were conducted with 25 participants , and data wereanalyzed using the Granheim and Lundman method. The data were managed using the MAXQDAsoftware (version 10.0).Results: Based on our analysis, the theme "Dual role of the patients' companion" and its two categories,"Companion as a facilitator" and "Companion as an inhibitor", were extracted. Emotional support,satisfaction of basic needs, care arm, alarm bell, and communication bridge were the sub-categories ofthe first category, and Interfering with care and creation of tension were those of the second category.Conclusion: We concluded that the patients' companions can play an important role in transitionalcare, especially as emotional support and system assistants due to the structure of the health caresystem and Iranian cultural context . Therefore, it is suggested that the patients' companion should beconsidered as a member of the transition team and accompany them in this process by informing andsupporting them.